IGF2 mRNA Binding Protein 2 Transgenic Mice Are More Prone to Develop a Ductular Reaction and to Progress Toward Cirrhosis - Czepukojc, Beate; Abuhaliema, Ali; Barghash, Ahmad; Tierling, Sascha; Naß, Norbert; Simon, Yvette; Körbel, Christina; Cadenas, Cristina; van Hul, Noemi; Sachinidis, Agapios; Hengstler, Jan G.; Helms, Volkhard; et al. (Frontiers in Medicine, 2019)
The insulin-like growth factor 2 (IGF2) mRNA binding proteins (IMPs/IGF2BPs) IMP1 and 3 are regarded as oncofetal proteins, whereas the hepatic IMP2 expression in adults is controversially discussed. The splice variant IMP2-2/p62 promotes steatohepatitis and hepatocellular carcinoma. Aim of this study was to clarify whether IMP2 is expressed in the adult liver and influences progression toward cirrhosis. IMP2 was expressed at higher levels in embryonic compared to adult tissues as quantified in embryonic, newborn, and adult C57BL/6J mouse livers and suggested by analysis of publicly available human data. In an IMP2-2 transgenic mouse model microarray and qPCR analyses revealed increased expression of liver progenitor cell (LPC) markers Bex1, Prom1, Spp1, and Cdh1 indicating a de-differentiated liver cell phenotype. Induction of these LPC markers was confirmed in human cirrhotic tissue datasets. The LPC marker Spp1 has been described to play a major role in fibrogenesis. Thus, DNA methylation was investigated in order to decipher the regulatory mechanism of Spp1 induction. In IMP2-2 transgenic mouse livers single CpG sites were differentially methylated, as quantified by amplicon sequencing, whereas human HCC samples of a human publicly available dataset showed promoter hypomethylation. In order to study the impact of IMP2 on fibrogenesis in the context of steatohepatitis wild-type or IMP2-2 transgenic mice were fed either a methionine-choline deficient (MCD) or a control diet for 2-12 weeks. MCD-fed IMP2-2 transgenic mice showed a higher incidence of ductular reaction (DR), accompanied by hepatic stellate cell activation, extracellular matrix (ECM) deposition, and induction of the LPC markers Spp1, Cdh1, and Afp suggesting the occurrence of de-differentiated cells in transgenic livers. In human cirrhotic samples IMP2 overexpression correlated with LPC marker and ECM component expression. Progression of liver disease was induced by combined MCD and diethylnitrosamine (DEN) treatment. Combined MCD-DEN treatment resulted in shorter survival of IMP2-2 transgenic compared to wild-type mice. Only IMP2-2 transgenic livers progressed to cirrhosis, which was accompanied by a strong DR. In conclusion, IMP2 is an oncofetal protein in the liver that promotes DR characterized by de-differentiated cells towards steatohepatitis-associated cirrhosis development with poor survival.